Probabilities of discrepancy between minima of cross-validation, vapnik bounds and true risks - Klęsk, Przemysław (Zielona Góra: Uniwersytet Zielonogórski)
Two known approaches to complexity selection are taken under consideration: n-fold cross-validation and structural risk minimization. Obviously, in either approach, a discrepancy between the indicated optimal complexity (indicated as the minimum of a generalization error estimate or a bound) and the genuine minimum of unknown true risks is possible. In the paper, this problem is posed in a novel quantitative way.
Keywords: regression estimation; model comparison; complexity selection; cross-validation; generalization; statistical learning theory; generalization bounds; structural risk minimization